DIGITAL MODELING OF WHEAT AND SOYBEAN PRODUCTION BASED ON ECONOMIC AND MATHEMATICAL METHODS - Ekaterina Vladimirovna Berdnova (Science and Innovation Center Publishing House, 2019)
In modern conditions of import substitution, the question of domestic production of crop products, including soybeans, is acute. Of course, soybeans is grown in Russia, but there are no suitable tools to optimize its production. There is an increasing need to obtain the greatest profit from the sale of soybeans, but there is no competent planning of acreage for various crops, including soybeans.